Differential expression of granulopoiesis related genes in neutrophil subsets distinguished by membrane expression of CD177. - Nan Hu (Public Library of Science (PLoS), 2014)
Objective Differential gene expression in CD177+ and CD177- neutrophils was investigated, in order to detect possible differences in neutrophil function which could be related to the pathogenesis of ANCA-associated Vasculitides (AAV). Methods Neutrophils were isolated from healthy controls (HC) with high, negative or bimodal CD177 expression, and sorted into CD177+ and CD177- subpopulations. Total RNA was screened for expression of 24,000 probes with Illumina Ref-8 Beadchips. Genes showing differential expression between CD177+ and CD177- subsets in microarray analysis were re-assessed using quantitative-PCR. CD177 expression on neutrophil precursors in bone marrow was analyzed using quantitative PCR and flowcytometry. Results The proportion of CD177+ cells increased during neutrophil maturation in bone marrow. Fold change analysis of gene expression profile of sorted CD177+ and CD177- neutrophils resulted in 14 genes with fold change (fc) >3 difference in expression. Interestingly, 10 of these genes have been reported to change significantly in expression during neutrophil maturation, and most of these genes were granule protein (GP) coding genes. mRNA expression levels measured by RT-PCR of a number of these GP, and of PR3 and MPO were higher in the CD177- neutrophil subset in HC, however, particular granule protein amounts were comparable between CD177+ and CD177- neutrophil subsets. AAV patients had higher amounts of CD177+ neutrophils, but contrary to neutrophils from HC expression of GP-genes was increased, possibly due to activation. Conclusion The neutrophil population can be distinguished by membrane expression of CD177 into subsets that are different in expression of GP mRNA but not in GP protein production. GP gene expression is also elevated in AAV patients, which is not explained by skewed distribution of CD177+ and CD177- subsets but may be associated with neutrophil activation during on-going inflammation.